Economically feasible decarbonization of the Haber-Bosch process through supercritical CO2 Allam cycle integration. (1st February 2022) - Byun, Manhee; Lim, Dongjun; Lee, Boreum; Kim, Ayeon; Lee, In-Beum; Brigljević, Boris; Lim, Hankwon
Graphical abstract: Highlights: Novel concept for supercritical CO2 -Haber-Bosch integrated process is presented. Comprehensive process simulation in Aspen Plus of two distinct design cases. Techno-economic analysis at scales of 1.5, 15, and 150 ton h −1 NH3 is performed. Both cases of the integrated process show profitability at scales >5 ton h −1 NH3 . Significant gaseous CO2 emission reduction of 68%-96% compared to conventional HB. Abstract: The well-established Haber-Bosch (HB) process (industrial ammonia production) is a significant contributor to the world's carbon emissions as it is a major consumer of natural gas as well as being energy-intensive in general. This work addresses the challenge of decarbonizing the HB process in a novel way as it, for the first time, presents a conceptual process integration with a supercritical CO2 Allam power cycle, therefore transforming gaseous CO2 emissions into a valuable side product in a form of liquid CO2 . Detailed process design and flowsheet simulation using Aspen Plus ® was used as a basis for scale-up and techno-economic assessment of two cases (electrical grid dependent and independent). The results indicated that using this process design NH3 production reaches profitability at scales larger than 2 ton h −1 to 5.4 ton h −1 and at current global NH3 prices, the cost of manufacturing decrease, due to scale-up stabilizes at ∼ 30 ton h −1 . Finally, this novel process integration achieves a significant reduction in gaseous CO2 emissions (compared to conventional HB process) of 68 % to 96 %, which indicates great potential for economically feasible green NH3 .